1987
DOI: 10.1021/ic00264a001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and reactivity of transition metal/main group metal bridging carboxylate complexes of the formula (.eta.5-C5H5)Re(NO)(PPh3)(CO2MLn) (M = Li, K, Ge, Sn, Pb)

Abstract: Metal-C02 complexes have attracted attention from both fundamental and applied viewpoints.1 First, C02 is an abundant Q molecule that serves as nature's photosynthetic building block.Second, C02 exhibits a variety of binding modes to metals.1"6 Third, the reactivity of metal-C02 complexes should provide insight regarding C02 activation and the design of new catalytic reactions.7 We have previously described the synthesis of the Scheme I. Representative Syntheses and Reactions of Rhenium/ Main-Group-Metal Bridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 4 publications
2
28
0
Order By: Relevance
“…The Sn---O bond lengths in this molecule differ by 0.219 A [2.123 (4) and 2.342(4) A]. The difference is considerably greater than observed (Senn et al, 1987) for the related compound CpRe(NO)(PPha)CO2SnPh3 (0.082 A) but smaller than that observed for monomeric triaryltin organocarboxylates (Holmes, Day, Chandrasekhar, Vollano & Holmes, 1986) (Johnson, 1965) plot of compound showing the atomic numbering system. The thermal ellipsoids are drawn at the 50% probability level.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The Sn---O bond lengths in this molecule differ by 0.219 A [2.123 (4) and 2.342(4) A]. The difference is considerably greater than observed (Senn et al, 1987) for the related compound CpRe(NO)(PPha)CO2SnPh3 (0.082 A) but smaller than that observed for monomeric triaryltin organocarboxylates (Holmes, Day, Chandrasekhar, Vollano & Holmes, 1986) (Johnson, 1965) plot of compound showing the atomic numbering system. The thermal ellipsoids are drawn at the 50% probability level.…”
Section: Discussionmentioning
confidence: 70%
“…Selected bond lengths (A) and angles (°) are given in Table 2. The structure is isomorphous with the related compound CpRe(NO)(PPha)CO2SnPh3 (Senn, Gladysz, Emerson & Larsen, 1987) (space group Pcab) with some minor differences. The Sn---O bond lengths in this molecule differ by 0.219 A [2.123 (4) and 2.342(4) A].…”
Section: Discussionmentioning
confidence: 99%
“…Each tin atom has pseudotetrahedral geometry (SnCbRe, SnCkCRe or SnC2ClRe) and the rhenium atoms are sandwiched by cyclopentadienyl groups. The Sn-O bond distances are not equal, differing by 8.2 pm in the case shown [109] and much larger at 30.7 pm in the other [110]. Here the bridge is seen to be CO2 molecule bridging in a μ-η -CO2 fashion by both Ο atoms to Sn an the C atom to Re.…”
Section: Figure 2 Structure Of [Chbusn^-v-s2cpcy 3 )([I-cimo(co)2(pcmentioning
confidence: 83%
“…There are six examples with tin and rhenium [107][108][109][110], with a direct Sn-Re bond in four of them [107,108] with distances ranging from 260.9(1) to 279.3(1) pm (ave. 267 pm). Each tin atom has pseudotetrahedral geometry (SnCbRe, SnCkCRe or SnC2ClRe) and the rhenium atoms are sandwiched by cyclopentadienyl groups.…”
Section: Figure 2 Structure Of [Chbusn^-v-s2cpcy 3 )([I-cimo(co)2(pcmentioning
confidence: 99%
“…To the best of our knowledge, in 1987, Gladysz et al reported the first X-ray characterization of a transition metal/tin bridging CO 2 complex by isolating (η-C 5 H 5 )Re(NO)(PPh 3 ) (CO 2 SnPh 3 ) (16) [72]. Compound 16 was obtained in high yield (86%) by reacting (η-C 5 H 5 )Re(NO)(PPh 3 )(CO 2 K) with 1.1 equivalent of Ph 3 SnCl at −78 • C in THF (Scheme 23).…”
Section: X-ray Crystal Structuresmentioning
confidence: 99%